234k views
4 votes
Factor out the GCF:
-36n^3 + 6n^2

User Aemxdp
by
8.1k points

1 Answer

3 votes

Answer:

Explanation:

36n³ = 2 * 2 * 3 * 3 * n * n *n

6n² = 2*3 * n * n

GCF = 2 * 3 * n * n = 6n²

-36n³ = 6n² * (-6n)

-36n³ + 6n² = 6n²*(-6n) + 6n²

= 6n² ( -6n + 1)

User Jake Jones
by
8.0k points

Related questions

asked Jun 27, 2022 76.5k views
Johnymachine asked Jun 27, 2022
by Johnymachine
8.7k points
2 answers
2 votes
76.5k views
asked Sep 2, 2022 187k views
TehTris asked Sep 2, 2022
by TehTris
8.0k points
1 answer
22 votes
187k views
2 answers
1 vote
41.5k views